Synthesis and Characterization of Copper Oxide Nanoparticles Isolated from Acmella oleracea and Study of Antimicrobial and Phytochemical Properties - Dhungana, Sujan; Gauli, Anusa; Tiwari, Laxmi; Khadka, Devendra; Gautam, Surendra Kumar; Pokhrel, Megh Raj; Baral, Janaki; Poudel, Bhoj Raj (Amrit Research Journal, 2024)
This study utilized a green synthesis approach to produce CuO nanoparticles employing flower extract of Acmella oleracea where plant-derived biomolecules served as natural reducing and stabilizing agents. The synthesized nanoparticles were characterized through X-ray diffraction (XRD), UV-Vis spectroscopy, and Fourier Transform Infrared (FTIR) analysis. XRD suggested the monoclinic phase of nanoparticles that belong to the C2/c space group with a crystallite size of 17.35 nm on average. The band gap was calculated using the Tauc model which was 2.27 eV. Phytochemical screening confirmed the presence of alkaloids, essential for nanoparticle formation, through Mayer’s, Dragendorff’s, Wagner’s, and Hager’s tests. Antimicrobial tests showed that the CuO nanoparticles had significant activity against microbes such as Escherichia coli, Staphylococcus aureus, and Candida albicans, with inhibition zones of 1.5 to 1.8 cm. These findings highlight the potential of Acmella oleracea mediated CuO nanoparticles for biomedical and environmental applications.